KONSUMSI DAN PRODUKSI TELUR AYAM KEDU - SRI PARYANTI WALUYO; DARJONO DARJONO (Research Center for Biology-Indonesian Institute of Sciences, 1986)
SRI PARYANTI WALUYO & DARJONO. 1986. Consumption and egg production of Kedu Fowl.Berita Bioiogi 3(4): 181 - 184. Four females and three males of Kedu Fowl has been subjected to an observation on egg production and consumption. The fowl was reared in individual cage for 68 days during the laying period.The observation revealed that the female consumed feed and water on an average of 94.645 gr and 254.45 ml a day respectively while the male was on an average of 105.96 gr and 294.91 ml a day.The manuvre production by the female fowl was recorded 85.81 gr per day. During the period of observation the average egg lay.ed by the female fowl was 34 eggs.In this period, the average weigt body gain on the female was 233.33 gr and on the male 41.66 gr respectively.In respect to the efficiency or raising Kedu fowl,feed and water in take.bodygain and egg production are considered important. These parameters are suggested to be applied as a basic selection of Kedu in a cage.